Land use and coverage dynamics of São Pedro village fishermen community territory, Jaramataia, Alagoas, Brazil - Farias, José Lucas Nunes de; Oliveira, Matteus Freitas de; Pereira, Jackson Belo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
This work aimed to carry out a survey and classification about the uses and land cover in the territory of the fishing community of the São Pedro village in Jaramataia, Alagoas, using geoprocessing as a support. For this, the LANDSAT 8 image, scene 215/067, was used, which was processed using unsupervised and supervised algorithms using the Envi 5.3 software. For the unsupervised classification, the interpolation generated 7 classes that presented several data conflicts. For the supervised, eight classes were identified and characterized: steppe wooded savannas, secondary steppe savannas, seasonal wooded steppe, temporary crop or pasture, permanent crop, exposed soil, urban area and water bodies with emphasis on artisanal fishing. With that, it was observed that the area has a high degree of anthropization and the relevant patch of native vegetation is concentrated in the most accentuated elevation levels of the difficult to access relief. This study opens the possibility for the management of the territory based on the appropriation of information from the areas of use and coverage and the generation of public policies that promote local development based on sustainable actions.